A Combined Bioinformatics and Chemoinformatics Approach for Developing Asymmetric Bivalent AMPA Receptor Positive Allosteric Modulators as Neuroprotective Agents. Issue 2 (20th December 2012) - Chen, Haijun; Wang, Cheng Z.; Ding, Chunyong; Wild, Christopher; Copits, Bryan; Swanson, Geoffrey T.; Johnson, Kenneth M.; Zhou, Jia
<x xml:space="preserve">Abstract</x> PAMs new in town! An effective, combined bioinformatics and chemoinformatics approach was applied to the design of novel asymmetric bivalent α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA) receptor positive allosteric modulators (PAMs) with marked potency in vitro and efficacy in vivo for preventing neuroapoptosis. The novel chemotype could provide pharmacological probes and potential therapeutic agents for glutamatergic hypofunction and its related neurological and psychiatric disorders.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>